The Model Of Small-Medium Creative Industries Food And Beverage Welfare: The Engineering Approach - Munadjat Wardoyo, Benedictus Kombaitan (International Journal of Advanced Science and Technology, 2020)
Background: West Java is a tourist destination in Indonesia, because it has a variety of attractions, both natural tourism objects, tourism heritage, as well as culinary tour. One of the tourist destination that is rich in objects and tourist attraction is the Bandung. Every year, always an increase in the number of tourists visiting Bandung. Bandung, has a wide range of food products and beverages, which can serve as one of the tourist destinations, especially culinary tourism. The purpose is to design in culinary-based tourism development model in order to increase the welfare of small medium-sized creative industries food-drink.